Age-specific parental knowledge of restraint transitions influences appropriateness of child occupant restraint use. Issue 3 (3rd June 2008) - Bilston, L E; Finch, C; Hatfield, J; Brown, J
Abstract : Objective: To determine the factors that influence appropriate restraint usage by child occupants across the age range for which any type of child restraint may be appropriate (0–10 years). Design: Randomized household telephone survey. Setting: Statewide survey, New South Wales, Australia. Subjects: Parents or carers of children aged 0–10 years. Main outcome measures: Parental reporting of appropriateness of child restraint. Methods: Demographic information and data on age, size, restraint practices, parental knowledge of child occupant safety, and attitude to restraint use was collected using a structured interview. Data were analysed using logistic regression after cluster adjustment. Results: Inappropriate restraint use by children was widespread, particularly in children aged 2+ years. Overall, parental knowledge of appropriate ages for restraint transitions was associated with increased likelihood of appropriate restraint use. Lower levels of formal parental education, larger families, parental restraint non-use, and parent/child negotiability of restraint use were predictors of inappropriate restraint use. For particular child age subgroups, the parental knowledge that predicted appropriate restraint use was specific to that age group. Most parents felt that they knew enough to safely restrain their child, despite widespread inappropriate restraint use. Conclusions: Parents are more likely to make appropriate restraint choices for their children if they possess restraint knowledge specific to their children's age and size. Educational campaigns may be most effective when they provide information for specific ages and transition points. Strategies to overcome parents' misplaced confidence that they know enough to restrain their children safely are also indicated.